Evaluasi Pendidikan Dan Pelatihan (DIKLAT) Pengadaan Barang Dan Jasa Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Surabaya - Satrio, Satrio Adji Syahidillah; Lestari, Yuni (Universitas Negeri Surabaya, 2023)
Evaluation of goods/services procurement training has a very important role in goods/services procurement training activities, because goods/services procurement training and training evaluation activities function as a benchmark for the success of the training. This research aims to describe the evaluation of training and training for the procurement of goods/services at the Personnel and Human Resources Development Agency of the Surabaya City Government using Suhariadi's (2013) 4level Kirkpatrick Model Evaluation theory, namely: Reaction Evaluation, Learning Evaluation, Behavioral Evaluation, and Results Evaluation. This research found incidents in the field that some employees who have the authority to manage finances and carry out goods and services procurement activities do not yet have certification and delays in completing the administration of goods/services procurement are due to the lack of knowledge and expertise possessed by employees. The qualitative research method is descriptive and uses observation, interview and documentation techniques. The technique used to analyze data in this research is through data collection, data reduction and drawing conclusions. The reaction evaluation has gone well, where the materials and facilities provided are in accordance with the specified specifications. The learning evaluation has had a good impact such as a change in the knowledge possessed by the participants. This is also shown in the behavioral evaluation where the participants feel a change in their behavior. The evaluation of the results showed poor results because there were still many participants who did not pass the certification. The suggestions given by researchers in this study are that the leadership of each agency requires employees who have duties to carry out financial management and procurement of goods/services, training organizers can provide varied materials and questions, training alumni can maintain good behavior, participants are given time lag that can be used to review the material. Keywords: Training Evaluation, Procurement of Good and Services